HPV and RAD51 as Prognostic Factors for Survival in Inoperable Oral and Oropharyngeal Cancer in Patients Unfit for Chemotherapy Treated with Hyperfractionated Radiotherapy - Zděblová Čermáková, Zuzana; Hurník, Pavel; Konvalinka, David; Štembírek, Jan; Paračková, Tereza; Resová, Kamila; Cvek, Jakub; Blažek, Tomáš; Knybel, Lukáš; Formánek, Martin; Gachechiladze, Mariam; Joerger, Markus; et al. (Medicina (Kaunas, Lithuania), 2023)
INTRODUCTION: The incidence of advanced oral cavity and oropharyngeal cancers is generally high. Treatment outcomes for patients, especially those unfit for comprehensive cancer treatment, are unsatisfactory. Therefore, the search for factors to predict response to treatment and increase overall survival is underway. OBJECTIVE: This study aimed to analyze the presence of 32 HPV genotypes in tumor samples of 34 patients and the effect of HPV status and RAD51 on overall survival. METHOD: Tumor samples of 34 patients with locally advanced oropharyngeal or oral cavity cancer treated with accelerated radiotherapy in monotherapy were analyzed using reverse hybridization and immunohistochemistry for the presence of HPV and RAD51. Its effect on overall survival was examined. RESULTS: Only two types of HPV were identified-HPV 16 (dominant) and HPV 66 (two samples). The HPV positivity was associated with a borderline insignificant improvement in 2-year (p = 0.083), 5-year (p = 0.159), and overall survival (p = 0.083). Similarly, the RAD51 overexpression was associated with borderline insignificant improvement in 2-year (p = 0.083) and 5-year (p = 0.159) survival. CONCLUSION: We found no statistically significant differences but detected trends toward improvement in the survival of HPV-positive and RAD51 overexpressing patients unfit for surgical treatment or chemotherapy treated with hyperfractionated radiotherapy. The trends, however, indicate that in a larger group of patients, the effects of these two parameters would likely be statistically significant.
Keywords: spinocelulární karcinom; oral cavity cancer; RAD51; Prognosis; lidský papilomavirus 6; Oropharyngeal Neoplasms; Papillomavirus Infections; nádory orofaryngu; rekombinasa Rad51; infekce papilomavirem; prognóza; Humans; Human papillomavirus 6; oropharyngeal cancer; radiotherapy; Rad51 Recombinase; HPV; Carcinoma, Squamous Cell; lidé